ASSESSING EFL STUDENTS' POLITENESS COMPETENCE IN THE REALIZATION OF REQUESTS - SINTA DEWI, - (2018)
This study investigates the EFL students' politeness competence in performing request acts to hearers with different power and distance, and with different ranks of imposition. The study also explores the students' perceptions on the concept of politeness in the context of requesting. Conducted under mix-method design, this study took up 10 undergraduate students as a sample group and utilized role-play tasks and interview to collect the data. The data from the former were analysed quantitatively using 5-point rating scales which later were justified by qualitative analysis. The other data were analysed by using Creswell's (2012) qualitative framework analysis. The findings indicated that the students' abilities to utilize contextually appropriate language were not fully developed. Their politeness competence was acknowledged as somewhat appropriate. Despite the fact, their comprehension on the concept of polite requests showed differently. The students understand that polite requests are context-dependent. Its realization relies on speakers' abilities to use linguistic expressions which are appropriate to the socio-contextual variables underlying the request situations. This implies that there was a gap between their comprehension and actual production which may be caused by several factors including their linguistic inadequacy and their native language norms. The study offers pedagogical implication as well as suggestions for further research. ---Penelitian ini dilakukan untuk melihat kompetensi kesantunan mahasiswa Bahasa Inggris dalam melakukan tindak tutur meminta (request) kepada orang yang memiliki power dan distance yang berbeda. Penelitian ini juga dilakukan untuk melihat persepsi mahasiswa terhadap konsep kesantunan dalam tindak tutur meminta (request). Penelitian ini menggunakan desain Mixed-Method dan melibatkan 10 mahasiswa S1 jurusan Bahasa Inggris sebagai subjek penelitian. Data dikumpulkan menggunakan tehnik role-play dan juga melalui wawancara. Data dari role-play dianalisa secara kuantitatif menggunakan skala penilaian (5-point rating scales) dengan kriteria yang sudah ditentukan. Sementara, data dari wawancara dianalisa secara kualitatif menggunakan kerangka analisis dari Creswell (2012). Hasil penelitian menunjukan bahwa kemampuan mahasiswa dalam menggunakan Bahasa yang tepat secara kontekstual belum sepenuhnya terbangun. Kompetensi kesantunan mereka diperkirakan masih berada pada level tidak terlalu tepat atau somewhat appropriate. Meskipun demikian, mahasiswa tersebut memiliki pemahaman yang cukup baik terhadap konsep kesantunan. Mereka memahami bahwa realisasi tindak tutur meminta (request) yang sopan itu sangat tergantung pada konteks penggunaannya. Hal ini menunjukan bahwa ada perbedaan antara persepsi siswa dan performa kesantunannya. Penelitian ini memberikan rekomendasi untuk praktis pengajaran serta untuk penelitian lain.